Las instituciones argentinas de educación superior, ¿impulsan la sostenibilidad? (Investigaciones) - Arias Valle, María Belén (2024)
This study examines how Argentine Higher Education Institutions (HEIs) integrate sustainability into their educational programs, aligned with Agenda 2030 and Law 27621 on Comprehensive Environmental Education. A cross-sectional descriptive quantitative study was carried out on 132 HEIs, evaluating their educational offer in sustainability. The results reveal that 54% of HEIs incorporate at least one teaching modality related to sustainability, highlighting the areas of environmental management and renewable energies. However, there is a notable disparity between provinces, with Buenos Aires, Santa Fe and Mendoza leading in the educational offer, while other regions present a limited offer. Furthermore, there is a higher prevalence of bachelor’s and master’s degree programmes compared to courses, specialisations, diploma and doctoral programmes. Public HEIs have a higher share of sustainability education than private HEIs. The study concludes that, although there is a significant commitment to sustainability, policies and strategies need to be implemented to improve regional equity and diversify the educational offer. It recommends developing regulations, practical guidelines and training programmes, as well as fostering collaboration between institutions and ensuring adequate funding to support these initiatives.